Best Paper Selection (Yearbook of Medical Informatics, 2021)
Gemein LAW, Schirrmeister RT, Chrabąszcz P, Wilson D, Boedecker J, Schulze-Bonhage A, Hutter F, Ball T. Machine-learning-based diagnostics of EEG pathology. https://www.sciencedirect.com/science/article/pii/S1053811920305073?via%3DihubKarimi D, Dou H, Warfield SK, Gholipour A. Deep learning with noisy labels: Exploring techniques and remedies in medical image analysis. https://www.sciencedirect.com/science/article/abs/pii/S1361841520301237?via%3DihubLangner T, Strand R, Ahlström H, Kullberg J. Large-scale biometry with interpretable neural network regression on UK Biobank body MRI. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7576214/Saito H, Aoki T, Aoyama K, Kato Y, Tsuboi A, Yamada A, Fujishiro M, Oka S, Ishihara S, Matsuda T, Nakahori M, Tanaka S, Koike K, Tada T. Automatic detection and classification of protruding lesions in wireless capsule endoscopy images based on a deep convolutional neural network. https://www.giejournal.org/article/S0016-5107(20)30132-2/fulltext